Alpha richness and niche breadth of a widespread group of aquatic insects in Nearctic and Neotropical streams - McCreadie, John William; Hamada, Neusa; Grillet, Maria Eugenia; Adler, Peter H. (Freshwater Biology, 2017)
The increase in species richness from the poles to the equator is one of the most consistent biogeographical patterns of species distributions. Using a globally distributed group of stream insects–black flies (Diptera: Simuliidae)–we addressed two questions: (i) How does α-richness vary among streams of the New World? (ii) Does niche width, as measured by a proxy based on stream-habitat conditions, differ between the Nearctic and Neotropical regions? In our analyses of α-richness, we consider the potential effects of area, elevation, sample size and season. Examining 296 streams in 12 regional collections, we found that α-richness differed little among New World streams. Using stream variables to delineate a measure of niche breadth, we also found no difference in the mean niche breadth of species between North and South America. Our results are consistent with niche conservatism. In other words, as black flies expanded into the tropics, their mean niche breadth did not contract relative to that of their northern counterparts. © 2016 John Wiley & Sons Ltd